The The Influence Of Barista And Product On The Store Atmosphere And Its Impact On Coffee Shop Customer Satisfaction In The Lowland - Wachdijono Wachdijono; Nelia Fariani Siregar Nelia Fariani Siregar; Sukree Langputeh; Akhmad Jaeroni (Journal Of Social Science (JoSS), 2023)
Coffee shops are businesses in the downstream agribusiness subsystem proliferating in various countries. This growth has created competition, so every coffee shop tries to Win it by giving more satisfaction to its consumers. The research aims to analyze the influence of baristas and products on the store atmosphere and its impact on coffee shop consumer satisfaction in the plains. The research location is in Cirebon City, Province West Java, Indonesia, because the city can represent the geographical conditions of world cities in the lowlands where many coffee shops stand. The research will be carried out in August–December 2023. The research design uses descriptive quantitative survey methods. The sample size was set at 100 coffee shop consumers in Cirebon City an accidental sampling technique. Measurement of indicators for each variable uses a Likert Scale. The data analysis technique uses Structural Equation Modeling. Research results conclude that the barista and the product each directly influence the store atmosphere, and the store atmosphere directly affects coffee shop consumer satisfaction. Baristas and products indirectly impact consumer satisfaction through the store atmosphere. The indicator that best reflects the condition of the barista variable is "accuracy," the product variable is "availability of product stock," and the store atmosphere variable is "coffee drinking room."